Combining 2′-fucosyllactose and galacto-oligosaccharides exerts anti-inflammatory effects and promotes gut health - Sewon Park; Yoonhee Park; Yu-Jin Jeong; Jun Gu Oh; Hee Joon Yoo; Jiyeon Yang; Jung-il Kwon; Kwang-Won Lee (Journal of Dairy Science, 2024)
ABSTRACT: This study investigated the potential of 2′-fucosyllactose (2′-FL) and galacto-oligosaccharides (GOS) combinations as a novel and cost-effective substitute for human milk oligosaccharides (HMO) in promoting gut health and reducing inflammation. In vitro studies using caco-2 cells showed that 2′-FL and GOS combinations (H1 = GOS:2′-FL ratio of 1.8:1; H2 = GOS:2′-FL ratio of 3.6:1) reduced LPS-induced inflammation by decreasing pro-inflammatory markers, whereas individual treatments had no significant effects. In a mouse model of dextran sulfate sodium (DSS)-induced colitis, combined 2′-FL and GOS supplementation alleviated symptoms, improved gut permeability, and enhanced intestinal structure, with the GH1 group (H1 combo with DSS) being the most effective. 2′-Fucosyllactose and GOS combinations also enhanced short-chain fatty acid production in infant fecal batch fermentation and mouse fecal analysis, with GH1 showing the most promising results. The GH1 supplementation altered gut microbiota in mice with DSS-induced colitis, promoting microbial diversity and a more balanced Firmicutes to Bacteroidota ratio. Infant formula products (IFP) containing 2′-FL and GOS combinations (IFP2 = 174 mg of GOS and 95 mg of 2′-FL per 14 g serving, 1.8:1 ratio; IFP3 = 174 mg of GOS and 48 mg of 2′-FL per 14 g serving, 3.6:1 ratio) demonstrated gastrointestinal protective and anti-inflammatory properties in a co-culture model of caco-2 and THP-1 cells. These findings suggest that 2′-FL and GOS combinations have potential applications in advanced infant formulas and supplements to promote gut health and reduce inflammation.